Highly flat optical comb generation based on DP‐MZM and phase modulators. Issue 1 (1st January 2019) - Tran, T.T.; Song, M.; Song, M.; Seo, D.‐S.
Abstract : A novel scheme for the generation of an optical frequency comb with exceptionally high flatness for a large number of spectral lines is proposed. The scheme consists of a dual‐parallel Mach–Zehnder modulator (DP‐MZM) with which to carve the narrow intensity pulse and phase modulators for the application of high chirp. The experimental results show perfect spectral profiles with 35 lines with <1 dB flatness and 54 lines at 1.6 dB flatness when a DP‐MZM is combined with two and three phase modulators, respectively.